Circularly Polarized Rectangular Microstrip Patch Antenna with Diagonal Asymmetric Slits - D, Sugumar; G, Thennarasi; Jones T, Anita; P T, Vanathi; N, Jency; Bosco, Jenifer (International Journal of Engineering and Technology, 2018)
In this paper, the circularly polarized rectangular microstrip patch antenna with asymmetric slits was proposed for Radio Frequency Identification (RFID) applications. The investigation was done over the whole S-band frequency (2-4 GHz) and found favor with the operating frequency of 2.4GHz which is very much suitable for RFID applications. Circular polarization was acquired by presenting four asymmetric slits along the diagonal corners of the microstrip patch with appropriate angles. An additional parasitic element was also introduced opposite to feed face to improve bandwidth and impedance matching. The performance of the proposed antenna was analyzed and compared for three different substrates namely Rogers (É›r =2.2), RT-DUROID (É›r =2.33), and FR4 (É›r =4.4). All the designs were simulated using CADFEKO 7. Detailed analysis carried out on all the three substrates to obtain circular polarization (axial ratio = 1) with desired parameters of return loss (>-10 dB), VSWR (<2), and gain (>2 dB). The experimental results conclude that the FR4 is the optimum choice and it proficiently meets the desired specifications.Â Â